PENERAPAN MODEL PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD INPRES LANSOT - Tuerah, Roos M. S.; Lengkong, Milinia K. S.; Manawan, Stelly V. (DIKSAR : Jurnal Pendidikan Dasar, 2023)
This study aims to improve student learning outcomes in Social Studies Class V Students of SD Inpres Lansot by applying the Talking Stick learning model. This type of research is Classroom Action Research. The data collection technique was carried out with observation and test techniques. This research was conducted in two cycles, where in the first cycle student learning outcomes only reached 64.2% so it was continued in the second cycle, which improved the learning process so that student learning outcomes increased to 94.2%. From these results the researcher can conclude that the use of the Talking Stick learning model can improve the learning outcomes of Class V students of SD Inpres Lansot in social studies subjects.